Propriale und nichtpropriale Sprachareale: Einheit in der Vielfältigkeit - Kloferová, Stanislava (Slavia Centralis, 2020)
Proprial and non-proprial language areas: unity in diversityProprial and non-proprial areals are manifestations of how one language functions. Despite differences between them (unique vs. general), this fact can be mutually made use of. The contribution demonstrates how the relation between the nucleus and the periphery of a non-proprial areal can help in linguistic analysis of uncertain, isolated proper names (anoikonyms) and how it can contribute towards finding their origin.
Keywords: dialectology; onomastics; linguistic areal; folk etymology